Orthodoxy, liberalism, and adaptation essays on ways of worldmaking in times of change from biblical, historical and systematic perspectives - Becking, Bob 1951- (Leiden Boston Brill, 2011)
Liberalism and Orthodoxy can only be succesfull as strategies for coping with change in society when they will be able to outline a recognisable and authentic framework for religiously informed pratcises and ethics
From introduction: proceedings of a symposium, "Coping with the changed/changing reality", held in Feb. 2008 at the Conference Centre "Bovendonck" in southern Netherlands. - Includes bibliographical references and indexes. - Description based on print version record
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Change -- Congresses -- Religious aspects; Change -- Congresses; Religion and culture -- Congresses; Adaptability (Psychology) -- Congresses; Adjustment (Psychology) -- Congresses; Liberalism; Change -- Congresses; Religion and culture -- Congresses; Adaptability (Psychology) -- Congresses; Adjustment (Psychology) -- Congresses; Change -- Religious aspects -- Congresses; RELIGION ; Fundamentalism; Adaptability (Psychology); Adjustment (Psychology); Change; Change ; Religious aspects; RELIGION ; Christian Theology ; Process; Religion and culture; Conference papers and proceedings; Electronic books -- Conference proceedings; Konferenzschrift